Pessoa com transtorno do espectro do autismo (TEA), dignidade humana e atendimento socioeducacional: um olhar para as percepções familiares - Strelhow, Thyeles Moratti Precilio Borcarte (2014)
Autism Spectrum Disorder (ASD) makes up a broad and complex universe with difficulties related to the areas of behavior, of social interaction and of communication. The lack of a biological marker demands that the diagnostic take place through clinical observation and, in most cases, it presents a challenge to the professionals responsible for making the diagnosis. The most common treatment approaches are: Treatment and Education of Autistic and Communication Handicapped Children (TEACCH), Applied Behavior Analysis (ABA) and Picture Exchange Communication System (PECS), based on behaviorist theories. These programs are related to the development of routines, of skills for daily use and of communication strategies. In the context of the family, the disorder demands a reorganization and planning around the care of the person with ASD. Confronted with this reality the discussion of human dignity is set as a necessary reflection and mainly related to human rights which are constituted as concrete. Thus, the constitution of human dignity as imago Dei is established in the relation of the human being with the Creator, with the human and with all of creation. In the area of human rights, historically constituted, it is also possible to discuss human dignity as a constitutive process of the human being through communal interaction, through otherness, through recognition and participation which aims at the visibility of the people in their specific characteristics. This form of understanding human dignity seeks to situate it beyond a mere prop and aims at truly contributing to the advancement of practices in public policies. In this way it becomes possible for the rights related to the socio-educational treatment of persons with ASD to be transformed into real actions. Thus, understanding the analysis of the content of the interviews carried out with family members of persons with ASD, it becomes evident that issues such as: adequate socioeducational treatment; capacitated and willing professionals for care; and effective public policies constitute essential elements pointed out by the family members for the daily development of the person with ASD.